CONTRASTING CLINICAL MANIFESTATIONS OF HERPES ZOSTER IN IMMUNOCOMPETENT CHILDREN: TWO CASE REPORTS - Hardjo Lugito, Manuel Dwiyanto; Sumendap, Indira Betari; Pratiwi, Theresia Dhearine; Herawati, Margaretha; Satya, Brammadita (Dentino: Jurnal Kedokteran Gigi, 2026)
Background: Herpes zoster (HZ) is uncommon in pediatric population. Severe disseminated forms like Herpes Zoster Multiplex (HZM)—involving non-contiguous dermatomes—are rare but can occur in immunocompetent pediatric patients, despite HZ usually being benign. Objective: We report two contrasting clinical presentations of HZ in immunocompetent pediatric patients to highlight its clinical variability and the critical need for individualized therapeutic strategies. Cases: Case 1 describes a 9-year-old girl with a history of varicella presenting with classic HZ on the right lower lip. She experienced a mild course and recovered with supportive topical treatment. Case 2 describes an 8-year-old girl with no known varicella history presenting with severe HZM involving trigeminal, cervical, and thoracic dermatomes. CaseManagement: She required hospitalization for oral acyclovir, intravenous corticosteroids, and antibiotics. The condition resolved without lethal complications, resulting only in keloid sequelae. Both patients demonstrated non-anemic macrocytosis. Conclusion: Recognizing the clinical variability of HZ in pediatric patients is essential. Differentiating severe disseminated forms like HZM from classic HZ is critical, as HZM necessitates aggressive systemic therapy and hospitalization, compared to the outpatient supportive care often sufficient for classical presentations. Keywords:Acyclovir; Herpes Zoster Multiplex; Immunocompetent; Oral Medicine; Trigeminal